Assessment of Robert Sweeny, Why Did We Choose to Industrialize? Montreal 1819–1849 - MCPHERSON, KATHRYN (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
In Robert Sweeny’s book Why Did We Choose to Industrialize?, changing gender relationships between women and men constitute one of the “tension-filled relationships” embroiled in Montreal’s transition to an industrial economy. My paper assesses the author’s success in mobilizing feminist scholarship in his analysis, both in terms of the book’s content and its form.